2022
DOI: 10.1098/rstb.2021.0128
|View full text |Cite
|
Sign up to set email alerts
|

A global and regional view of the opportunity for climate-smart mariculture

Abstract: Food systems and the communities they support are increasingly challenged by climate change and the need to arrest escalating threats through mitigation and adaptation. To ensure climate change mitigation strategies can be implemented effectively and to support substantial gains in greenhouse gas emissions reduction, it is, therefore, valuable to understand where climate-smart strategies might be used for best effect. We assessed mariculture in 171 coastal countries for vulnerabilities to climate change (12 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…Other studies have recommended a revision of the GFSI to make it more efficient and robust [42][43][44]. In the same vein, some studies have conducted assessments of national food security performances using the GFSI and indicators of sustainability [41,43,45,46], economic development [47][48][49], governance [38,50,51], and food sovereignty variables like inclusivity [52][53][54], resiliency [55][56][57][58], sufficiency, local production, collective action [59,60], sustainable finance (access to funds, diversified financial products, and financial literacy) [61][62][63][64] and food literacy [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have recommended a revision of the GFSI to make it more efficient and robust [42][43][44]. In the same vein, some studies have conducted assessments of national food security performances using the GFSI and indicators of sustainability [41,43,45,46], economic development [47][48][49], governance [38,50,51], and food sovereignty variables like inclusivity [52][53][54], resiliency [55][56][57][58], sufficiency, local production, collective action [59,60], sustainable finance (access to funds, diversified financial products, and financial literacy) [61][62][63][64] and food literacy [65].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most farmed seaweed is used as food, either consumed directly or as a food additive 13 , 15 , but in some economies (i.e., South Korea) seaweeds are increasingly being funneled into secondary production of abalone, also for human consumption 16 . Recent estimates have suggested that between 48 and 119 million km 2 of the global ocean (an area 24–60 times the size of Greenland) may be suitable for seaweed production 5 , 17 , however the industry remains nascent in most countries 5 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…We also conduct a preliminary assessment of economic feasibility. We applied our model to a case study in Canada, a nation identified to have extensive—but unexplored—potential to develop seaweed aquaculture for climate mitigation purposes 18 , 58 .…”
Section: Introductionmentioning
confidence: 99%
“…Seaweed aquaculture currently accounts for 29% of the global aquaculture production by weight (FAO 2022) with the vast majority (over 99%) currently grown in Asia [21,39] . Recent estimates have suggested that between 48-119 million km 2 of the global ocean (an area 24-60 times the size of Greenland) may be suitable for seaweed production [5,40] , however the industry remains nascent in most countries [5,41] . Farming seaweeds also has other potential benefits including reducing excess anthropogenic nutrients in ocean water, nourishing coastal ecosystems, and reducing wave impacts on shorelines [4,42,43] .…”
Section: Introductionmentioning
confidence: 99%
“…We consider several CO2 sequestration and emissions pathways with a focus on production and processing emissions, and marine sequestration. We applied our model to a case study in Canada, a nation identified to have extensive -but unexplored -potential to develop seaweed aquaculture for climate mitigation purposes [41,46] .…”
Section: Introductionmentioning
confidence: 99%